Pengembangan Alat Ukur Self Compassion pada Mahasiswa - Nadia Khoerunnisa; Denada Martantri; Sabila Ar Rifqi; Rafi Faishal Ariq; Kezia Safa Andrena; Tazkiyah Aulia Fatimah (IBERS : Jurnal Pendidikan Indonesia Bermutu, 2022)
In the transition phase of late adolescence to early adulthood, students are required to accept and control the negative emotions they experience for the problems that arise. In that case, this research wants to see how the scale created can measure self- compassion in students. This research focuses on developing a self-compassion measurement tool for students. The methods used in this research are quantitative methods and reading literature. The research sample obtained using non-probability sampling method with purposive sampling technique. The results of this study obtained 15 items which became the final item with a Likert-scaled model and equipped with concurrent validity analysis against other overlapping scales. This Self Compassion scale shows a significant correlation with the Academic Integrity scale. Then the validity and reliability values obtained are quite large, namely 0.88 and 0.84. It was found that the development of a self-compassion measuring instrument is a valid and reliable measuring instrument in measuring student self-compassion.